Revitalizing the School Museum: Using Nature-Based Objects for Cross-Curricular Learning. (3rd July 2021) - Cornish, Caroline; Driver, Felix; Nesbitt, Mark; Willison, Julia
ABSTRACT: This article analyzes an educational initiative between Kew Gardens, Royal Holloway, University of London, and two London primary schools. The schools, located in areas of high ethnic diversity, worked with the members of the Mobile Museum project team – including the Learning Department at Kew and researchers at both institutions – to create their own school museums. The idea was inspired by historical research conducted by the project team that demonstrated Kew's historic involvement in the promotion of object-based learning in schools. The project team worked with teachers and pupils to develop a participatory approach to learning about plants and their uses through the creation of school museums. A whole-school framework was adopted, extending the potential reach of the project to pupils' parents and communities. Inspired by the collections at Kew, schools used plants and plant-associated artifacts to learn more about the rich diversity of pupils' cultural backgrounds and the importance of plants to their heritage and their everyday lives.